PENGARUH PENEMPATAN KERJA, KOMPENSASI DAN BUDAYA ORGANISASI TERHADAP KINERJA KARYAWAN PADA PT RHB SEKURITAS KANTOR PUSAT WISMA MULIA BUILDING JAKARTA SELATAN - Jana Sandra (POLITEKNIK LP3I JAKARTA, 2022)
This research aims to analyze the effect of work placement, compensation and organizational culture on employee performance at PT RHB Sekuritas which is a securities company supervised by the Financial Services Authority (OJK). The population in this study were 141 employees of PT RHB Sekuritas. The sampling method is simple random sampling with a sample of 104 people. The data analysis technique used in this study is multiple regression analysis. Data processing in this study uses SPSS software version 25. The results show that work placement and organizational culture has a significant effect on employee performance in line with research by Rori, Mekel and Ogi (2014) and Research Awadh and Alyahya (2013), while compensation is not significant effect on employee performance in line with research by Riannsari (2012). .Keywords: Job placement, compensation, organizational culture, employee performance